Posterior Reversible Encephalopathy Syndrome Following Orthotopic Liver Transplantation for Sickle Hepatopathy - Ganesh, Nisha; Dave, Apeksha; Alebrahim, Musab; Chen, Wei; Yearsley, Martha; Elkhammas, Elmahdi; Washburn, Ken; Kitchens, William; Schenk, Austin (Archives of Clinical and Medical Case Reports, 2020)
Posterior reversible encephalopathy syndrome (PRES) occurs with increased frequency in solid organ transplant recipients and sickle cell disease patients. Sickle hepatopathy patients who require liver transplantation may be at markedly increased risk for developing PRES in the post-operative setting. Here, we describe two such cases and carefully consider causative factors.